DIFFERENCES IN SOME PARAMETERS OF SITUATION EFFICIENCY BETWEEN WINNING AND DEFEATED TEAMS AT TWO LEVELS OF COMPETITION - Alen Kapidžić; Elvedin Mejremić; Jasmin Bilalić; Ervin Bečirović (Sport Scientific And Practical Aspects, 2025)
The main objective of this research is to determine the frequency of application of technical - tactical elements of soccer game, that estimate interaction of players, offensive and defensive elements of the game, which we determine to what variables are the winning teams superior by comparison with defeated, in this two levels of competition. For the purposes of this study (research), analyzed are the games national teams that participated at the European Football EURO 2008, in Austria and Switzerland, and teams that competed in the Premier League of Bosnia and Herzegovina in the 2008/2009 season. For the purposes of this study (research), we used T-test for small independent sample. The results obtained within this study (research) indicate the following: The results clearly indicate what would inferior teams, this especially applies for the teams that compete in the Premier Leagueof B&H, should improve the technical-tactical elements, with greater emphasis on the situational variation to execute the same.This should reduce the possibility of tactical surprise of the match, because the team met with a number of problem situationsat the game. For the defeated teams of the Premier League stands, need to improve interaction between players in order to better co-operation during the transition from defense to attack. Improving of individual and group tactics in order to achieve higher frequency of attacks and the arrival in to position for kicking the opponent's goal.National teams that participated at the European Championship in 2008, differ in the variables of shooting at goal, so we can say:Defeated teams should raise the level of individual and group tactics, of which largely depends on the creation of positions for shooting at goal.